Ready for a fight? The physiological effects of detecting an opponent's pheromone cues prior to a contest - Garcia, M. J.; Williams, J.; Sinderman, B.; Earley, R. L. (Physiology & Behavior, 2015)
Reception of pheromone cues can elicit significant physiological (e.g. steroid hormone levels) changes in the recipient. These pheromone-induced physiological changes have been well documented for male-female interactions, but scarcely in same-sex interactions (male-male and female-female). We sought to address this dearth in the current literature and examine whether mangrove rivulus fish (Kryptolebias marmoratus) could detect and, ultimately, mount a physiological response to the pheromone signature of a potential, same-sex competitor. We examined steroid hormone levels in mangrove rivulus exposed to one of three treatments: 1) isolation, 2) exposure to pheromones of a size-matched partner, and 3) pheromone exposure to a size-matched opponent followed by a physical encounter with the opponent. We found that exposure to a competitor's pheromone cues elicited a significant increase in testosterone levels. Increases in testosterone were similar across genetically distinct lineages derived from geographically distinct populations. Further, testosterone levels were similar between individuals only exposed to pheromone cues and individuals exposed to both pheromone cues and a subsequent physical encounter. Our findings led us to generate a number of testable predictions regarding how mangrove rivulus utilize pheromone signals in social interactions, the molecular mechanisms linking social stimuli and hormonal responses, and the possible adaptive benefits of hormonal responsiveness to receiving a potential competitor's pheromone cues.